2017
DOI: 10.3389/fmars.2017.00340
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production by Seagrass Ecosystems in the Red Sea

Abstract: Atmospheric methane (CH 4 ) is the second strongest greenhouse gas and it is emitted to the atmosphere naturally by different sources. It is crucial to define the dimension of these natural emissions in order to forecast changes in atmospheric CH 4 mixing ratio in future scenarios. However, CH 4 emissions by seagrass ecosystems in shallow marine coastal systems have been neglected although their global extension. Here we quantify the CH 4 production rates of seagrass ecosystems in the Red Sea. We measured cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
1
45
1
1
Order By: Relevance
“…Methane (CH 4 ), after CO 2 the most important of greenhouse gases, is to a large degree emitted from wetlands, which can contribute as much as 30%-50% of the global emissions (Bridgham, Cadillo-Quiroz, Keller, & Zhuang, 2013;Laanbroek, 2009;Stocker et al, 2013;Whiting & Chanton, 1993). How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, 2015;Barber & Carlson, 1993;Deborde et al, 2010;Garcias-Bonet & Duarte, 2017;Oremland, 1975). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon-Durocher, Hulatt, Woodward, & Trimmer, 2017;Yvon-Durocher, Montoya, Woodward, Jones, & Trimmer, 2011), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias-Bonet, & Duarte, 2019;Lyimo et al, 2017), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias-Bonet & Duarte, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane (CH 4 ), after CO 2 the most important of greenhouse gases, is to a large degree emitted from wetlands, which can contribute as much as 30%-50% of the global emissions (Bridgham, Cadillo-Quiroz, Keller, & Zhuang, 2013;Laanbroek, 2009;Stocker et al, 2013;Whiting & Chanton, 1993). How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, 2015;Barber & Carlson, 1993;Deborde et al, 2010;Garcias-Bonet & Duarte, 2017;Oremland, 1975). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon-Durocher, Hulatt, Woodward, & Trimmer, 2017;Yvon-Durocher, Montoya, Woodward, Jones, & Trimmer, 2011), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias-Bonet, & Duarte, 2019;Lyimo et al, 2017), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias-Bonet & Duarte, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, 2015;Barber & Carlson, 1993;Deborde et al, 2010;Garcias-Bonet & Duarte, 2017;Oremland, 1975). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon-Durocher, Hulatt, Woodward, & Trimmer, 2017;Yvon-Durocher, Montoya, Woodward, Jones, & Trimmer, 2011), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias-Bonet, & Duarte, 2019;Lyimo et al, 2017), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias-Bonet & Duarte, 2017). In general, the methane production of biological systems is closely correlated with the productivity of the plants within the system (Borges, Speeckaert, Champenois, Scranton, & Gypens, 2018;Bridgham et al, 2013), and for wetlands in particular, there is a clear positive correlation between emission of methane and net ecosystem production (Whiting & Chanton, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The required instrumentation is more compact, portable, and cost-effective (Berden et al 2000;Crosson et al 2002). Moreover, it can be reliably operated on board research vessels to monitor the isotopic signal of stable isotopes (Becker et al 2012;Bass et al 2014;Garcias-Bonet and Duarte 2017); therefore becoming a competent alternative to common mass spectrometric analysis (Balslev-Clausen et al 2013). However, although laser absorption spectroscopic techniques offer compelling benefits, to the best of our knowledge, it has not been used to measure phytoplankton 13 C-primary production rates in the sea.…”
mentioning
confidence: 99%
“…We determined the relationship between metabolic rates and temperature by fitting an ordinary least squares linear regression equation to the re-lationship between the natural logarithm of the Chl a-specific metabolic rates (B 0 ) and the inverse of the absolute temperature × k (i.e. 1/kT ), where k is the Boltzmann's constant (8.617734 × 10 −5 eV K −1 ) (Gillooly et al, 2001;Brown et al, 2004):…”
Section: Net Community Metabolism Community Respiration and Gross Pmentioning
confidence: 99%
“…The metabolic theory of ecology (MTE) relates the metabolic rate of an organism with its mass and temperature. This theory hypothesises that individual metabolic rates relate to temperature with a relatively constant activation energy (E a ∼ 0.63 eV) for a wide range of taxa, from unicellular organisms to plants and animals (Gillooly et al, 2001;Brown et al, 2004). For aerobic respiration, E a values vary between 0.41 and 0.74 eV at temperatures between 0 and 40 • C , while for photosynthetic processes the predicted E a is lower, ∼ 0.32 eV .…”
Section: Temperature and Metabolic Balance In The Red Seamentioning
confidence: 99%